About a case of purulent pleuropericarditis - Visca, Pedro; Bogdan, Magdalena; Rissoto, Beatriz; Nese, Martha (Cirugía del Uruguay, 1982)
A patient developed purulent pleuropericarditis secondary to a metapneumonic empyema, although neither local nor general conditions favouing the process existed. There follows a discussion of its etiology and most frequent pathogenic mechanisms.